Book reviews - Levine, Paul; Frank, Margit; Ihanus, Juhani; Harviainen, Tapani; Karvonen, Lauri; Sundback, Susan; Martola, Nils; Illman, Karl-Johan (Nordisk judaistik/Scandinavian Jewish Studies, 1992)
Forging a new self: the Adamic protagonist and the emergence of a Jewish-American author as revealed through the novels of Bernard Malamud (Pirjo Ahokas, 1991) is reviewed by Paul Levine.EN TREUER KETZER. Studien zu Manès Sperbers Romantrilogie "We eine Träne im Ozean" (Claudia Sternberg, 1991, diss.) is reviewed by Margit Frank.Vilna on the Seine. Jewish intellectuals in France since 1968 (Judith Friedlander, 1990) is reviewed by Juhani Ihanus.Suomen juutalaisten aseveljeys (Hannu Rautakallio, 1989) is reviewed by Tapani Harviainen.Karaites and dejudaization. A historical review of an endogenous and exogenous paradigm (Roman Freund, 1991) is reviewed by Tapani Harviainen.Hakkorset och Wasakärven. En studie av nationalsocialismen i Sverige 1924–1950 (Heléne Lööw, 1990) and Führerns trogna följeslagare. Den finländska nazismen 1932–1944 (Henrik Ekberg, 1991) are reviewed by Lauri Karvonen.Juden in der Soziologie. Eine öffentliche Vortragsreihe an der Universität Konstantz 1989 (ed. Erhard R. Wiehn, 1989) is reviewed by Susan Sundback.Bibeln: tillägg till gamla testamentet: de apokryfa eller deuterokanoniska skrifterna (1986) and God och nyttig läsning: om gamla testamentets apokryfer (P. Block, J. Blomqvist, G-B Sundström, C. Åsberg, 1988) are reviewed by Nils Martola.Tradition og nybrud: jødedommen i hellenistisk tid (eds. Troels Engberg-Pedersen, Niels Lemche, 1990) is reviewed by Nils Martola.Short notice by Nils Martola.Jerusalem ja Rooma (Pauli Huuhtanen, 1989) is reviewed by Nils Martola.Minnen och tankar (Bruno Bettelheim, 1991) is reviewed by Karl-Johan Illman.Jødiske høytider i evangelisk lys (Dag Bughaug, 1991) is reviewed by Karl-Johan Illman.Antisemitismen. En historisk skildring i ord och bild (Hans Jansen, Janrense Boonstra, Joke Kniesmeyer, 1991) is reviewed by Karl-Johan Illman.Kyrkan och det judiska folket (Svenska kyrkans mission, 1991) is reviewed by Karl-Johan Illman.Mellan ord och tystnad. Essäer (Mona Vincent, 1991) is reviewed by Karl-Johan Illman.